1968
DOI: 10.2307/1935530
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the New England Herring Gull Population

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.In the present study, however, this species overwintered in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
99
2
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(110 citation statements)
references
References 25 publications
6
99
2
3
Order By: Relevance
“…Working on related species, Hunt and Hunt (1976) have shown that heavier chicks have a higher survival rate, and Briggs (1977) has shown that early hatched gull chicks tend to be larger and socially dominant over smaller and later-hatched chicks at food sources during the winter. It is generally agreed that the first winter is crucial in determining survival of young gulls, because this is when they suffer their highest rate of mortality (Kadlec and Drury 1968, Spaans 1971, Coulter 1975, Briggs 1977. In fact, mortality during this period may be higher than during the 1st wk of life, which is considered to be the time when the highest mortality rate occurs in most species (compare Kadlec and Drury 1968: Table 22 with Hunt and Hunt 1976: Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Working on related species, Hunt and Hunt (1976) have shown that heavier chicks have a higher survival rate, and Briggs (1977) has shown that early hatched gull chicks tend to be larger and socially dominant over smaller and later-hatched chicks at food sources during the winter. It is generally agreed that the first winter is crucial in determining survival of young gulls, because this is when they suffer their highest rate of mortality (Kadlec and Drury 1968, Spaans 1971, Coulter 1975, Briggs 1977. In fact, mortality during this period may be higher than during the 1st wk of life, which is considered to be the time when the highest mortality rate occurs in most species (compare Kadlec and Drury 1968: Table 22 with Hunt and Hunt 1976: Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that the first winter is crucial in determining survival of young gulls, because this is when they suffer their highest rate of mortality (Kadlec and Drury 1968, Spaans 1971, Coulter 1975, Briggs 1977. In fact, mortality during this period may be higher than during the 1st wk of life, which is considered to be the time when the highest mortality rate occurs in most species (compare Kadlec and Drury 1968: Table 22 with Hunt and Hunt 1976: Table 2). Because growth rate was shown to be positively correlated with prefledging survival of chicks in this study, gulls nesting in rocky habitat may produce more offspring that survive the first winter, even though they may not fledge more chicks at the end of the breeding period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To make informed decisions on landfill sitings and operations with regard to aircraft safety, more information is needed on the extent and pattern of daily bird use (feeding, soaring, loafing) of landfills and the area around landfills (Lake, 1984;McLaren et al, 1984;Risley and Blokpoel, 1984;Southern and Southern, 1984;Forsythe and Austin, 1984). In addition, we know little about the contribution that abundant dependable food at landfills has made to the overall population increases of gulls in many areas of North America (Kadlec and Drury, 1968;Ludwig, 1974;Blokpoel and Tessier, 1986).…”
mentioning
confidence: 99%